Association between blood lead levels and parathyroid hormone among United States adolescents aged 12–19: a cross-sectional study - He, Baomei; Wang, Xiaowei; Luo, Huanjun; Zhou, Qin (Frontiers in Endocrinology, 2024)
Aims: Studies on the association between serum lead levels and parathyroid function in adolescents are lacking. Therefore, in this study, we elucidated the possible association between blood lead levels (BLLs) and the parathyroid hormone (PTH) in adolescents aged 12–19 years in the United States. Methods: In this study, information from the database of the National Health and Nutrition Examination Survey was utilized. The study included 3919 participants from survey cycles between 2003–2004 and 2005–2006. Multivariable linear regression analysis was performed to determine the correlation between BLLs and PTH. Furthermore, smooth curve fitting was utilized to analyze the dose–response relationship between BLLs and PTH. Results: Multivariable linear regression analysis revealed that every 1 μg/dL increase in BLLs was associated with 0.67 pg/mL increase in PTH (β = 0.67, 95% CI: 0.16–1.18, p < 0.01). However, sex-stratified subgroup analysis revealed that this positive association was only observed in males (β = 1.16, 95% CI: 0.50–1.83 p < 0.01). Smooth curve fitting revealed a positive correlation between BLLs and PTH. Conclusions: In adolescents in the United States, BLLs are positively correlated with PTH, particularly in males.